Efficacy of Bio-Pesticides for Managegement of Sucking Insect Pests of Cotton, Gossipium hirsutum (L.) - Abdul Majeed Noonari; Ghulam Hussain Abro; Rab Dino Khuhro; Abdul Sattar Buriro (Journal of Basic & Applied Sciences, 2016)
The studies were conducted consecutively for two years, 2006 and 2007 for management of cotton insect pests through eco-friendly measures. Bio-pesticides Neem seed extract, Neem oil, Asafoetida (Hing) and Tobacco leaf extract were evaluated against sucking complex. The experiment regarding evaluation botanical pesticides showed that among all bio-pesticides, the highest percent reduction of thrip (67.65%) was recorded in Neem seed extract followed by Neem oil (60.00%), Tobacco (63.59%) and Hing (Asafoetida) (52.68%) after 96 h. of application. Overall maximum mean reduction (64.69%) was recorded in Neem seed extract followed by Neem oil (57.74%), Tobacco (52.91%) and Asafoetida (46.52%). The highest reduction of jassid (71.97%) was recorded followed by Neem oil (70.06%), Hing (Asafoetida) (68.15%) and Tobacco (23.56%) after 96 h., of application of pesticides. With regards to reduction percent of whitefly revealed that maximum reduction (60.18%) was recorded in Hing (Asafoetida) followed by Neem oil (59.78%), Neem extract (59.38%) and tobacco (40.61%) after 96 h., of spray application. The botanical pesticides started reducing their toxicity after 96 h. However, the effective reduction of pests was recorded up to one week. Integrated pest management (IPM) model was developed for the control of sucking insect pests of cotton, for benefit of farming community through seminars, trainings and pamphlets. Using the safe botanical pesticides remained effective against sucking pests and is recommended against cotton pests, which showed less effective to natural enemies and environment friendly.